Chile’s Citizenship Education Curriculum: Priorities and Silences Through Two Decades - Cox, Cristián; Garcia, Carolina (Encounters in Theory and History of Education / Rencontres en Théorie et Histoire de l'Éducation / Encuentros en Teoría e Historia de la Educación)

(untitled) (Faculty of Education, Queen's University, 2021)
The article examines the evolution of the citizenship education curriculum in Chilean secondary education over last two decades from the perspective of the relevance of its contents for a democratic culture. The evidence and its analysis show the variations observed in the curricula are not related so much to the ideology of the governments that enact them as to socio-cultural changes of a macro nature, such as the growing emphasis on rights and participation. The analysis confirms some deficits common to the curricula, which have implications for the development of the democratic political culture in Chile. Among these are the scarce or null presence of the values of solidarity, the common good, and social cohesion, as well as a paradox of quasi-silence about voting, common in the curricula of Latin American countries and which is contrasted with the treatment of voting in the curricula of France and England.